2019
DOI: 10.1002/ange.201813984
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric and Geometry‐Selective α‐Alkenylation of α‐Amino Acids

Abstract: Both E‐ and Z‐N′‐alkenyl urea derivatives of imidazolidinones may be formed selectively from enantiopure α‐amino acids. Generation of their enolate derivatives in the presence of K+ and [18]crown‐6 induces intramolecular migration of the alkenyl group from N′ to Cα with retention of double bond geometry. DFT calculations indicate a partially concerted substitution mechanism. Hydrolysis of the enantiopure products under acid conditions reveals quaternary α‐alkenyl amino acids with stereodivergent control of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Dieser jüngsten Arbeit vorangehend haben Clayden et al. umfangreiche alternative Anwendungen dieser Aryltransferreaktionen untersucht, insbesondere bei Ringexpansionsreaktionen, z. B. mit den Substraten 240 und 241 .…”
Section: Organische Umlagerungen üBer Spiro‐strukturen: Intermediat O...unclassified
“…Dieser jüngsten Arbeit vorangehend haben Clayden et al. umfangreiche alternative Anwendungen dieser Aryltransferreaktionen untersucht, insbesondere bei Ringexpansionsreaktionen, z. B. mit den Substraten 240 und 241 .…”
Section: Organische Umlagerungen üBer Spiro‐strukturen: Intermediat O...unclassified
“…We have recently described several reactions in which the N-chloroformyl derivative of an imidazolidinone plays a pivotal role, [15][16][17][18] and this work showed that the two diastereoisomers of these carbamoyl chlorides displayed very different reactivity. In one particular family of Bischler-Napieralski-like cyclisations, 16 only the trans isomer was of use.…”
Section: Scheme 1: Imidazolidinones As Intermediates In the Synthesis Of Quaternary Amino Acid Derivativesmentioning
confidence: 95%
“…Precursors: All esters, amides, and imines (precursors to the N-chloroformylimidazolidinones) were synthesised on 10-30 gram scale according to our previously reported literature protocols. [15][16][17]…”
Section: General Informationmentioning
confidence: 99%
See 2 more Smart Citations